The Kepler conjecture the Hales- Ferguson proof by Thomas Hales, Samuel Ferguson - Lagarias, Jeffrey C. 1949-; Ferguson, Samuel (Birkhäuser, 2011)
The Kepler conjecture, one of geometry's oldest unsolved problems. The Kepler conjecture states that the densest packing of three-dimensional Euclidean space by equal spheres is attained by the cannonball packing. This book centers around six papers, presenting the detailed proof of the Kepler conjecture.